Green School Project Sebagai Upaya Transformasi Sekolah Ramah Lingkungan Melalui Penghijauan - Reftyawati, Dian; Rahmawati, Ulfa Nur; Azzam, Ridho (PT. Sharia Journal and Education Center, 2026)
The lack of green spaces and limited ecological awareness among school members pose significant challenges in establishing an environmentally friendly school. This community service program aimed to transform school culture through the implementation of a Green School Project based on greening initiatives at SMPN 22 Bandar Lampung. The program was designed using a participatory approach involving the principal, teachers, students, and administrative staff. The implementation stages included planning, environmental literacy socialization, tree planting and garden arrangement practices, as well as mentoring and sustainability monitoring. Evaluation was conducted through participatory observation and documentation to identify both physical environmental changes and shifts in school members’ attitudes. The results indicated an improvement in the school’s physical environment through the addition of green areas and more structured garden management. Students’ active participation in plant maintenance increased, alongside stronger awareness of environmental cleanliness. The program also fostered collective commitment to sustaining greening activities. Therefore, the Green School Project proved effective as a strategy for transforming schools into environmentally friendly learning environments and holds potential for replication in similar contexts.